Integrated stratigraphy and facies analysis of the Upper Albian - Turonian (Cretaceous) Debarsu Formation (Yazd Block, Central Iran) - Wilmsen, Markus; Storm, Marisa; Fürsich, Franz; Majidifard, Mahmoud Reza (Strati 2013. First International Congress on stratigraphy. At the cutting edge of stratigraphy, 2014)
The upper Albian–Turonian Debarsu Formation in its type area around Haftoman, south of Khur (Central Iran), has been investigated using an integrated approach of detailed logging, biostratigraphic and sequence-stratigraphic dating, and facies analysis based on field observations and microfacies studies. The formation was deposited on a homoclinal carbonate ramp with a basinal area situated towards the north. Numerous shallowing-upward cycles from offshore marl to shallow-water limestones are capped by palaeokarst surfaces, providing evidence of significant relative sea-level changes. Based on the stratigraphic positions of the sequence-bounding unconformities, a predominantly eustatic control of the sedimentary cyclicity is inferred. The major unconformity at the base of the overlying Coniacian–Campanian Haftoman Formation, however, is of tectonic origin.
UnivIS-Import:2017-12-18:Pub.2014.nat.dgeo.IGM.LP.integr
Keywords: Albian; Turonian; Debarsu Formation; Haftoman; Khur; Coniacian; Campanian; Mid-Cretaceous; Biostratigraphy; Sequence stratigraphy; Homoclinal ramp; Geodynamics